A model for predicting photovoltaic module performances - Bouaziz, Nadia; Benfdila, Arezki; Lakhlef, Ahcene (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The present paper deals with the development of a simulation model for predicting the performances of a solar photovoltaic (PV) system operating under current meteorological conditions at the site location. The proposed model is based on the cell equivalent circuit including a photocurrent source, a diode, a series and shunt resistances. Mathematical expressions developed for modeling the PV generator performances are based on current-voltage characteristic of the considered modules. The developed model allows the prediction of PV cell (module) behavior under different physical and environmental parameters. The model can be extended to extract physical parameters for a given solar PV module as a function of temperature and solar irradiation. A typical 260 W solar panel developed by LG Company was used for model evaluation using Newton-Raphson approach under MATLAB environment in order to analyze its behavior under actual operating conditions. Comparison of our results with data taken from the manufacturer’s datasheet shows good agreement and confirms the validity of our model. Hence, the proposed approach can be an alternative to extract different parameters of any PV module to study and predict its performances.